2008
DOI: 10.1007/s00586-008-0786-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cervical nucleoplasty in the treatment of cervical disc herniation

Abstract: Percutaneous disc decompression procedures have been performed in the past. Various percutaneous techniques such as percutaneous discectomy, laser discectomy, and nucleoplasty have been successful. Our prospective study was directly to evaluate the results of percutaneous cervical nucleoplasty (PCN) surgery for cervical disc herniation, and illustrate the effectiveness of PCN in symptomatic patients who had cervical herniated discs. From July of 2002 to June of 2005, 126 consecutive patients with contained cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 24 publications
3
73
0
1
Order By: Relevance
“…Though pain as measured by VAS was significantly reduced in both the CC and PDD patients, the PDD group displayed statistically significantly greater pain reduction at all follow-up time points. In their patient series, Li et al [28] similarly reported statistically significant VAS pain reduction (P \ 0.01) after PDD when compared to preoperative values through all time points (2 weeks, 1, 3, 6, and 12 months). In our study, by just 6 weeks post-procedure, 84% of PDD patients had achieved a clinically important (MCID) reduction in radicular and neck pain; at no time points did an equivalent proportion of CC patients achieve a MCID reduction in their pain.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Though pain as measured by VAS was significantly reduced in both the CC and PDD patients, the PDD group displayed statistically significantly greater pain reduction at all follow-up time points. In their patient series, Li et al [28] similarly reported statistically significant VAS pain reduction (P \ 0.01) after PDD when compared to preoperative values through all time points (2 weeks, 1, 3, 6, and 12 months). In our study, by just 6 weeks post-procedure, 84% of PDD patients had achieved a clinically important (MCID) reduction in radicular and neck pain; at no time points did an equivalent proportion of CC patients achieve a MCID reduction in their pain.…”
Section: Discussionmentioning
confidence: 83%
“…Bonaldi et al [3] performed a prospective case study utilizing PDD to treat 55 patients with cervical disc herniations and symptoms of neck and arm pain; 85% of these patients had a good to excellent clinical outcome by 6 months post-procedure. More recently, Li et al [28] performed cervical PDD on 126 consecutive patients with similar results: a good to excellent clinical outcome of 83.73% by 1-year post-procedure. These early results suggest that cervical PDD may be an appropriate method to resolve pain symptoms in these patients before attempting open surgery, which can be accompanied by severe complications [2,15,16,43,56].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…1 Epstein suggests that there is negative risk-benefit ratio in the use of MIS cervical foraminotomies and favors the use of open techniques, 30 but it is our opinion that complications are avoided by eliminating use of guidewires to begin the process of soft tissue dilation. In 2008, MIS-ACDF using endoscopic techniques was reported by Ruetten et al 111 In the same year, anterior cervical nucleoplasty using percutaneous techniques in cadavers was described by Li et al 76 The use of MAST for cervical instrumentation has been described. Wang and colleagues 130 were the first to report on its clinical use in the placement of lateral mass screws.…”
Section: Disorders Of the Cervical Spinementioning
confidence: 99%
“…Only 2 out of 30 required surgical treatment, and this was apparent at 6 weeks. One can compare these results to those achieved by Li et al [39], in their paper describing percutaneous cervical nucleoplasty in the treatment of cervical disc herniation, I suspect that most patients and surgeons would opt for a selective root block, rather then having the inside of the disc burnt, and the risk of a piece of equipment being left in the disc! Kumar in his preoperative assessment measures the neck disability index, and shows that it reduces from an average of 66.9 to 31 at 6 weeks, with little reduction afterwards at a year.…”
Section: Supplement 1 April 2008mentioning
confidence: 98%